Knee Kinetics in Baseball Hitting and Return to Play after ACL Reconstruction - Giordano, Kevin; Chaput, Meredith; Anz, Adam; Braziel, Jeremy; Andrews, James; Oliver, Gretchen D. (International Journal of Sports Medicine, 2020)
The purpose of this study was to describe the knee kinetics of baseball hitting, develop a tool to predict knee kinetics from easily obtainable measures, and to compare knee kinetics to other exercises along the rehabilitation continuum to determine a timeline for when hitting may resume after ACL reconstruction. Nineteen high school baseball athletes (16.3±0.8 yrs, 180.6±5.7 cm, 78.4±10.8 kg) participated. Participants took ten swings off a tee. Kinetic data were recorded using an electromagnetic tracking system. Data from swings with the top three exit velocities were averaged for analysis. Linear regressions were used to determine if predictors of height, mass, age and exit velocity could predict the following torques: bilateral knee net, extension, internal and external rotation, valgus and varus torque; and anterior force. Backwards regression models revealed independent variables could significantly predict front knee net, internal and external rotation, extension, and varus torque, and anterior force; and back knee net and valgus torque. Based on the kinetics of baseball hitting compared to those of rehabilitation exercises, if the involved knee is the front, we suggest tee hitting may be initiated at 13 weeks after ACL reconstruction. If the involved knee is the back, we suggest tee hitting may initiated at 17 weeks after ACL reconstruction.
Keywords: ACL rehabilitation protocol; knee biomechanics; clinical measures; rehabilitation protocols; return to play